Personal finance - Kapoor, Jack R. 1937-; Dlabay, Les R.; Hughes, Robert James 1946- (New York, NY McGraw-Hill Education, 2017)
"The integrated solutions for Ross/Westerfield/Jaffe/Jordan's Corporate Finance: Core Principles and Applications have been specifically designed to help improve student performance, meaning that students are prepared for and engaged in class, and they can successfully solve problems and analyse the results. McGraw-Hill's adaptive learning component, LearnSmart, provides assignable modules that help students master chapter core concepts and come to class more prepared. In addition, resources within Connect help students solve financial problems and apply what they've learned. Ross' focus on the core concepts, cutting-edge research, and rich problem material combine with a complete digital solution to help students achieve higher outcomes in the course. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective"-- Provided by publisher.
"As authors and teachers, we believe it is important to help people develop a plan to achieve financial security. While the 12th edition of Personal Finance does not guarantee that each student will be able to get the ideal job or become a millionaire, it does provide the information needed to take advantage of opportunities and to help manage personal finances. As in previous editions, we address the changing financial needs and challenges that students face on a daily basis. The 12th edition of Personal Finance provides a wealth of information about career planning; money management; taxes; consumer credit, including college loans; housing; legal protection; insurance; investments; retirement planning; and estate planning. By teaching students how to make informed choices, we believe you can encourage them to build a foundation of financial security"-- Provided by publisher.
Revised edition of Personal finance, [2015]
Includes bibliographical references and index.
Keywords: Finance, Personal; BUSINESS & ECONOMICS / Personal Finance / General